Workload Analysis for Man Power Planning in PT Batuwangi Putera Sejahtera - Budiman, Yusuf; Putranto, Nur Arief Rahmatsyah (Journal of Business and Management, 2015)
Abstract. Business competition in Indonesia is growing rapidly. Generally, each company provides maximum treatment to the employees to improve efficiency and productivity aimed to achieve company goals. Every company has similar goal in terms of getting a significant advantage with the aid of existing human resources. Human resource planning is the analysis of the number of employees needed by a company (Stoner and Wankel, 1986). Thus, the company can make the right decisions to solve the problem of human resource needs through the analysis of workload. PT. Batuwangi Putera Sejahtera is a company engaged in the milling and mining of limestone. The workload in the company is not distributed evenly yet, which causes some divisions have excess work. Companies must provide appropriate workloads for employees to reduce employees stress while working. The purpose of this research is to find ways to conduct manpower planning for PT. Batuwangi Putera Sejahtera by using workload analysis as consideration. The method used in this research is direct sampling. This method is used because there is numerous number of employees and the employees are doing regular task. The expected result of this research is the better distribution of workload and optimal allocation of employees in PT. Batuwangi Putera Sejahtera. The findings of this research that has been resulted from 12 employees of PT. Batuwangi Putera Sejahtera showed that there are currently 3 employees who have a very high workload, 7 employees are thinking about high work load but can still be overcame, and 2 employees have the normal workload. From these results, it is suggested that PT. Batuwangi Putera Sejahtera adds 3 additional employees, so that the total number of employee is 15 people.Â Keywords: workload analysis, manpower planning